Batahemolitični streptokoki skupin B in G iz Pomurja - značilnosti izolatov, odpornih proti antibiotikom - Štrumbelj, Iztok (Zdravniški vestnik, 2003)
Background. Macrolide-resistant strains of betahemolytic streptococci have been isolated in Pomurje region in Slovenia. The aim of the study was to determine phenotypes of macrolide-lincozamide resistance and patterns of resistance to selected antibiotics in these isolates. Methods. Twenty-one erythromycin-resistant isolates from group B and group G beta-hemolytic streptococci, obtained from patients in Pomurje were analyzed. Phenotypes of macrolide-lincozamide resistance were determined in all isolates. In group B and group G streptococci susceptibility to 8 and 14 antibiotics was tested, respectively. Results. All 42 isolates were susceptible to penicillin and vancomycin. The majority of erythromycin-resistant group B streptococci isolates was tetracycline-resistant but susceptible to chloramphenicoland of loxacin. In erythromycin-resistant isalates of group G streptococci 5 different resistance patterns were found. The most frequent pattern was a resistance to multiple antibiotics (besides erythromycin also to midekamycin, clindamycin, tetracycline, chloramphenicol and several fluoroquinolones). Conclusions. These resistant isolates are unique and represent novel example of a strong bacterial ability to adapt to changes in their environment and consequently survive in the presence of antibiotics.
Keywords: antibiotic; Antibiotics, Macrolide; antibiotiki; Antibiotiki makrolidni; Chloramphenicol Resistance; Clindamycin; Drug Resistance, Microbial; Eritromicin; Erythromycin; Klindamicin; Kloramfenikolova rezistenca; Lateks, fiksacijski testi; Latex Fixation Tests; mikrobi; odpornost; Oflaksacin; Ofloxacin; Penicilinska rezistenca; Penicillin Resistance; Streptococcus; Streptococcus Agalactiae; streptokoki; Tetraciklinska rezistenca; Tetracycline Resistance; Zdravilo, rezistenca mikrobna